2018
DOI: 10.1051/matecconf/201815201008
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Dye in Wastewater by Adsorption-Coagulation Combined System with Hibiscus sabdariffa as the Coagulant

Abstract: The conventional process to treat dye wastewater is the physicochemical treatment such as coagulation, flocculation and adsorption process. A new approach has been demonstrated to treat Congo red dye wastewater, which is the adsorption-coagulation hybrid process. Natural coagulant extracted from Hibiscus sabdariffa seeds is used as the coagulant while activated carbon is used as the adsorbent in this case study. The objective of this experiment is to study the significant factors that will affect the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 12 publications
2
18
0
6
Order By: Relevance
“…GHC exhibited maximum color removal (90.13%) in an acidic condition (pH 5.5) when compared to the alkali condition, whereas PAC showed maximum color removal (94.38%) in an alkali condition (pH 8). Similar observation was reported for Hibiscus sabdariffa seeds used as a natural coagulant for dye removal . Trung et al examined the ability of Cassia fistula seed gum (CFG) as a coagulant in combination with synthetic PAC for the treatment of textile wastewater.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…GHC exhibited maximum color removal (90.13%) in an acidic condition (pH 5.5) when compared to the alkali condition, whereas PAC showed maximum color removal (94.38%) in an alkali condition (pH 8). Similar observation was reported for Hibiscus sabdariffa seeds used as a natural coagulant for dye removal . Trung et al examined the ability of Cassia fistula seed gum (CFG) as a coagulant in combination with synthetic PAC for the treatment of textile wastewater.…”
Section: Resultssupporting
confidence: 56%
“…Similar observation was reported for Hibiscus sabdariffa seeds used as a natural coagulant for dye removal. [39] Trung et al [37] examined the ability of Cassia fistula seed gum (CFG) as a coagulant in combination with synthetic PAC for the treatment of textile wastewater. The authors reported that CFG supplementation has improved the process efficiency, that is, nearly 98% color removal for RB21 and 90% color removal for MB at the optimum dose of CFG 0.15 and 0.1 mL, respectively.…”
Section: Color Removal Efficiency Of Biopolymeric and Synthetic Polymmentioning
confidence: 99%
“…Decorative plants are also used for the treatment of dye wastewater as Hibiscus sabdariffa is used to treat CR dye [15]. Ipomoea hederfolia plant is reported for treatment of Scarlet red dye [5].…”
Section: Introductionmentioning
confidence: 99%
“…The plant extract was obtained from Hibiscus Sabdariffa as shown Figure 1. Before this experiment, it is widely known that the hibiscus extract are used for flavours, medicinal, pharmaceuticals, agrochemicals, fragrances, treatment of wastewaters and local dyes [12][13][14][15]. The major component in the flower is the cyanidin 3-sophoroside.…”
mentioning
confidence: 99%